2007
DOI: 10.1681/asn.2006020124
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glomerular Maturation and Lack of VEGF165b in Denys-Drash Syndrome

Abstract: Individuals with Denys-Drash syndrome (DDS) develop diffuse mesangial sclerosis, ultimately leading to renal failure. The disease is caused by mutations that affect the zinc finger structure of the Wilms' tumor protein (WT1), but the mechanisms whereby these mutations result in glomerulosclerosis remain largely obscure. How WT1 regulates genes is likely to be complex, because it has multiple splice forms, binds both DNA and RNA, and associates with spliceosomes. Herein is described that in DDS podocytes, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 36 publications
(34 reference statements)
1
67
0
Order By: Relevance
“…Indeed, VEGF 165 b is expressed early in human kidney embryonic development, 20 although at a lower mRNA level than in the adult. 48 Although an effect on glomerular development might be postulated, nephrin (and therefore transgene) expression occurs relatively late in kidney development in rodents (day 18 of 21 in rats) 49 -that is, at the capillary loop stage. 50 In addition, it cannot be assumed that the differential permeability properties of VEGF 165 and VEGF 165 b in vessels are BASIC RESEARCH www.jasn.org maintained in the embryo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, VEGF 165 b is expressed early in human kidney embryonic development, 20 although at a lower mRNA level than in the adult. 48 Although an effect on glomerular development might be postulated, nephrin (and therefore transgene) expression occurs relatively late in kidney development in rodents (day 18 of 21 in rats) 49 -that is, at the capillary loop stage. 50 In addition, it cannot be assumed that the differential permeability properties of VEGF 165 and VEGF 165 b in vessels are BASIC RESEARCH www.jasn.org maintained in the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Even if this were the case, it is also unknown how their putative conflicting properties on embryonic endothelial cells may interact with the similarity of their cytoprotective effects on glomerular epithelial cells. 20 The finding that exon 8a containing conventional isoforms (e.g., VEGF 165 ) tend to predominate in de-differentiated human conditionally immortalized podocytes that lack exon 8b-containing isoforms, the latter being present in differentiated podocytes, prompted Schumacher et al 48 to suggest that podocyte maturation (GECs and hence the GBM) may depend on isoform family ratio. The study by Schumacher et al of VEGF isoform expression in DenysDrash syndrome (DDS; glomerular dysgenesis, male pseudohermaphroditism, FSGS, and uremia) showed that DDS podocytes produce ample proangiogenic, propermeability VEGF 165 but completely lack the antiangiogenic, antipermeability form VEGF 165 b.…”
Section: Discussionmentioning
confidence: 99%
“…Constituents of the glomerular basement membrane in DDS also resemble those of the S-shaped body stage and not those of differentiated adult glomeruli. The authors have interpreted this to mean that glomerular maturation is delayed in DDS, again in keeping with a failure to proceed fully through MET [69]. Whether this defect can be linked to disturbances of the RNA metabolism roles (+KTS isoforms) or transcriptional targets (−KTS isoforms) of WT1 has yet to be elucidated.…”
Section: Developmental Renal Diseasementioning
confidence: 99%
“…In differentiated podocytes, levels of exon 8b-containing VEGF predominate over exon 8a-containing isoforms 17 ; however, podocytes in patients with DenysDrash syndrome (Wilms' tumor, genital anomalies, and nephropathy) exhibit a reversal of this ratio. 18 Harper and colleagues 13 suggest that the Wilms' tumor-1 transcription factor, which is mutated in Denys-Drash, may influence the splicing of VEGF in podocytes because it acts as a repressor for a splice factor kinase and thereby downregulates VEGF165b.…”
mentioning
confidence: 99%
“…Moreover, all of the VEGF knockout studies to date are deletions of both pro-and antiangiogenic VEGF isoforms, thereby complicating interpretations of the phenotypic role played by each splice variant. Thus, future studies could settle this issue by deleting individual splice variants by knock-in of nonsplicing exon 8 18 containing constructs into the VEGF gene locus.…”
mentioning
confidence: 99%